Plastic reconstructive microsurgery in the elderly patient - Consensus statement of the German Speaking Working Group for Microsurgery of the Peripheral Nerves and Vessels - Ludolph, Ingo; Lehnhardt, Marcus; Arkudas, Andreas; Kneser, Ulrich; Pierer, Gerhard; Harder, Yves; Horch, Raymund E. (Handchirurgie, Mikrochirurgie, Plastische Chirurgie, 2018)
During the last two decades, understanding and experience of microsurgical reconstruction have increased. This is linked to improved instruments and technical devices, as well as to the increased number of available donor sites for microvascular flap transfer. If the indication is appropriate, it is now possible to perform personalised, safe and successful microsurgical reconstructions, almost independently of the patients' age. Despite these constant developments, there is little specific literature on microsurgery related to the specific problems of the elderly patient. During two consensus workshops organised by the DAM (German Speaking Working Group for Microsurgery of the Peripheral Nerves and Vessels), the latest findings and experience with microsurgical reconstruction in the elderly patient were presented by a group of experts and current recommendations were formulated. On the basis of these consensus workshops and the current literature, this article discusses important issues in this area.
EVALuna2:211479